Assessment of Nurse–Midwives’ Knowledge and Practices toward Second Stage of Labor - Rasheid, ahrar; ali, Rabea’a (Iraqi National Journal of Nursing Specialties, 2010)
Objective: To assess the nurses-midwives’ knowledge and practices regarding the management of second stage of labor and to find out the association between their knowledge and practices and socio-demographic characteristics and working years and experience. Methodology: A descriptive study was carried out from March 22nd , 2008 through 30th June, 2008. A purposive sample of (75) Nurse-Midwives which was selected from (6) hospitals. A questionnaire was comprised of two parts: (socio-demographic characteristics and the assessment tool for Nurse-Midwives’ knowledge and health practices performed by them). The questionnaire validity was determined by experts and its reliability was determined through a pilot study. The correlation coefficient was (0.90) for knowledge and (0.83) for practices. Data were collected through interview and observational tool and analyzed through the application of descriptive and inferential statistical approaches. Results: The study findings indicated that there was a high mean of scores in Nurse-Midwives’ knowledge and a low mean of scores for their practices in most of the items regarding second stage of labor. The study findings also indicated that there is a significant association between nurses-midwives’ practices and their educational level, and birth number average. Recommendations: The study recommends that; installing in-service educational program for Nurse-Midwives to upgrade the techniques necessary to assess, evaluate and improve the quality of care rendered to laboring women, and to put an emphasis on the Ministry of Health to conduct training course for the Nurse-Midwives in order to change their malpractices and updating their knowledge with regular supervision on their performance.